Type I IFN-dependent antibody response at the basis of sex dimorphism in the outcome of COVID-19. (April 2021) - Gabriele, Lucia; Fragale, Alessandra; Romagnoli, Giulia; Parlato, Stefania; Lapenta, Caterina; Santini, Stefano Maria; Ozato, Keiko; Capone, Imerio
Highlights: Sex-based outcome of SARS-CoV-2 infection accounts for about 70 % of male deaths, despite similar susceptibility to infection. TLR7/IFN-α axis in pDCs is crucial for B-cell activation and it is at the basis of dimorphic antibody response. Dysregulated and unbalanced IFN-driven B cell response affects COVID-19 outcome in males. Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the ongoing coronavirus disease 2019 (COVID-19) pandemic, induces severe pneumonia mainly in elderly males. Epidemiological data clearly indicate sex-based differences in disease outcomes, with men accounting for about 70 % of deaths, despite similar susceptibility to infection. It is well known that females are endowed with higher capacity to produce antibodies, which correlates with viral clearance and disease resolution in the context of SARS-Cov-2 infection. Many X-linked immune genes escape X inactivation showing biallelic expression in female immune cells, particularly in plasmacytoid dendritic cells (pDCs). PDCs are more active in females and endowed with high capability to induce IFN-α-mediated B cell activation and differentiation into antibody-producing plasma cells throughout epigenetic mechanisms linked to trained immunity. Thus, we hypothesize that following SARS-CoV-2 infection, epigenetic modifications of X-linked genes involved in pDC-mediated type I IFN (IFN-I) signaling occurs more effectively in females, for inducing neutralizing antibody response as an immune correlate driving sex-biased disease outcome.